Musculoskeletal Diseases 2017-2020 Diagnostic Imaging - Hodler, Juerg; Kubik-Huch, Rahel A.; von Schulthess, Gustav K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on with musculoskeletal imaging: during the last few years, there have been considerable advances in this area, driven by clinical as well as technological developments. The authors, internationally renowned experts in their field, have contributed chapters that are disease-oriented and cover all relevant imaging modalities, including magnetic resonance imaging, computed tomography, and positron emission tomography. As a result, this book offers a comprehensive review of the state of the art in musculoskeletal imaging. It is a valuable resource for general radiologists, radiology residents, rheumatologists, orthopaedic surgeons, and clinicians from other specialities wishing to update their knowledge in this discipline.
Adult Tumors: Soft Tissue, Bone, Bone Marrow -- Ankle and Foot -- Arthritis -- Elbow -- Hip -- Infection -- Knee -- Metabolic / Endocrine -- Muscle Imaging -- Pediatric MSK Trauma: What Is Unique and What Not To Miss -- Pelvis and Groin -- Peripheral Nerve Imaging -- Postoperative Knee -- Postoperative Knee and Shoulder -- Primary Bone and Soft Tissue Tumors in Children -- Shoulder: Instability -- Shoulder: Rotator Cuff -- Spine: Degeneration and Inflammation -- Spine: Trauma -- Ultrasonography: Sports Injuries -- Wrist and Hand. .
Keywords: Medicine; Radiology; Orthopedics; Medicine & Public Health; Imaging / Radiology; Orthopedics